115k views
4 votes
Convert the equation:


6x ^(2) - 3y ^(2) + 12x - 18y - 3 = 0
to the standard form of a hyperbola.


User SMKrizan
by
5.1k points

1 Answer

6 votes

Answer:

(x+1)²/6 - (y+3)²/12 = 1

Explanation:

The standard form of writing the equation of an hyperbola is expressed as;

(x-h)²/a² - (y-b)²/b² = 1 where (h,k) is the centre of the hyperbola.

Given the equation:

6x²-3y²+12x-18y-3 = 0

We are to convert it to the standard form of writing the equation of a hyperbola.

Collecting the like terms will give;

(6x²+12x)-(3y²+18y)-3 = 0

Divide through by 3

(2x²+4x)-(y²+6y)-1 = 0

Completing the square of the equation in parenthesis and adding the constants to the other side of the equation:

(2x²+4x)-(y²+6y+(6/2)²)-1 = 0+(6/2)²

(2x²+4x)-(y²+6y+9)-1 = 9

2x²+4x -{(y+3)²} = 9+1

2x²+4x - (y+3)² = 10

Divide through by 2

x²+2x -(y+3)²/2 = 5

(x²+2x+(2/2)²)-(y+3)²/2 = 5+(2/2)²

(x²+2x+1) - (y+3)²/2 = 5+1

(x+1)²-(y+3)²/2 = 6

Divide through by 6

(x+1)²/6 - (y+3)²/12 = 1

The resulting equation is the required standard form of a hyperbola with centre at (-1, -3)

User Quimby
by
4.6k points